Current Therapeutic Options for the Main Monogenic Autoinflammatory Diseases and PFAPA Syndrome: Evidence-Based Approach and Proposal of a Practical Guide - Soriano, Alessandra; Soriano, Marco; Espinosa, Gerard; Manna, Raffaele; Emmi, Giacomo; Cantarini, Luca; Hernández-Rodríguez, José (Frontiers in Immunology, 2020)
Monogenic autoinflammatory diseases are rare conditions caused by genetic abnormalities affecting the innate immunity. Previous therapeutic strategies had been mainly based on results from retrospective studies and physicians’ experience. However, during the last years, the significant improvement in their genetic and pathogenic knowledge has been accompanied by a remarkable progress in their management. The relatively recent identification of the inflammasome as the crucial pathogenic mechanism causing an aberrant production of interleukin (IL)-1β in the most frequent monogenic autoinflammatory diseases, led to the introduction of anti-IL-1 agents and other biologic drugs as part of the previously limited therapeutic armamentarium available. Advances in the treatment of autoinflammatory diseases have been favored by the use of new biologic agents and the performance of a notable number of randomized clinical trials exploring the efficacy and safety of these agents. Clinical trials have contributed to increase the level of evidence and provided more robust therapeutic recommendations. This review analyzes the treatment of the most frequent monogenic autoinflammatory diseases, namely familial Mediterranean fever (FMF), TNF-receptor associated periodic fever syndrome (TRAPS), hyperimmunoglobulin D syndrome/mevalonate kinase deficiency (HIDS/MKD), and cryopyrin-associated periodic syndromes (CAPS), together with periodic fever with aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome, which is the most common polygenic autoinflammatory disease in children, also occurring in adult patients. Finally, based on the available expert consensus recommendations and the highest level of evidence of the published studies, a practical evidence-based guideline for the treatment of these autoinflammatory diseases is proposed.